Cultural Identity in a Plate: Gastrolinguistic Insights into the Naming Strategy of Javanese Sega (Rice) Dishes - Siti Nurlina, Wiwin Erni; Setiyanto, Edi; Riani, Riani; Darmawati, Besse; Nurfaidah, Resti; Husnah, Wabilia; Abdulmalik, Irmayani; Irawan, Yusup; Sutarsih; Murdowo, Drajat Agus; Winarti, Daru; Yulianti, Saras (Forum for Linguistic Studies, 2025)
In Javanese society, sega (rice) forms the foundation of numerous traditional culinary dishes whose names carry profound cultural weight, often reflecting prayers, hopes, commemorations, or specific attributes. Despite widespread recognition of names’ cultural importance and the growing field of gastrolinguistics, a systematic analysis of the specific naming models and underlying strategies for naming Javanese sega dishes remains a discernible gap in existing literature. This study, therefore, aims to uncover these diverse naming models and strategies, revealing the cultural cognition embedded within Javanese culinary nomenclature, employing a qualitative descriptive method with findings presented through narrative, explanatory, and elaborative descriptions supported by validated observational and documentation data. The research successfully identified twelve core strategic concepts governing this nomenclature—including color, taste, shape, cooking method, condition/characteristic, main side dish/vegetable, arrangement/serving method, container, origin, acronymization, purpose, and combination—significantly contributing to gastrolinguistics, ethnolinguistics, and cultural studies by offering a nuanced framework for understanding culinary nomenclature in a specific cultural context and deepening insights into the interplay of language, culture, and food. Practically, its applications span cultural preservation, culinary education, and the promotion of Javanese culinary heritage, offering valuable insights for culturally sensitive food tourism, comparative studies of food naming across diverse cultures, and promoting broader global engagement with Javanese culinary heritage as a unique facet of a universally significant staple.